Development of Screw Feeder Hopper Nozzle of Direct- Write Deposition Applicable to Layer Manufacturing Process. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Development of deposition method is continuously conducted which is aimed to yield the smallest and the most accurate of line deposition. Some factors affect the dimension of line deposition, namely powder material, powder flow-ability, and parameters of deposition process: deposition gap and feed-rate. Flow-ability determines the dimensional continuity of line deposition. Generally, flow-ability depends on the particle shape, particle size, atmosphere condition and force which works inter particle. In this research we focused to observe powder flow-ability which caused by controlling screw feeder rotational speed and varying of particle size. The line deposition testing would be conducted with this flow-ability condition. Flow-ability and line deposition testing used stainless steel powder of 38-52, 52-75, 75-106 pm in diameter and duraform polyamide powder of 38-75 pm in diameter was used on line deposition testing. The results showed the stainless steel powder of 52-75 pm yielded the highest flow-ability. The result of feed-rate varying showed that the powder was not continuously spurt out from the nozzle, therefore the deposition process needs to find the best feed-rate.